The LysR‐type regulator SftR is involved in soil survival and sulphate ester metabolism in Pseudomonas putida - Antje Kahnert; Pascal Mirleau; Robin Wait; Michael A. Kertesz (Environmental Microbiology, 2002)
Summary Sulphate esters make up a large proportion of the available sulphur in agricultural soils, and many pseudomonads can desulphurize a range of aryl‐ and alkylsulphate esters to provide sulphur for growth. After miniTn 5 transposon mutagenesis of Pseudomonas putida S‐313, we isolated 19 mutants that were defective in cleavage of the chromogenic sulphate ester 5‐bromo‐4‐chloro‐3‐indoxylsulphate (X‐sulphate). Analysis of these strains revealed that they carried independent insertions in a gene cluster that comprised genes for a sulphate ester/sulphonate transporter ( atsRBC ) a LysR‐type regulator ( sftR ), an oxygenolytic alkylsulphatase ( atsK ), an arylsulphotransferase ( astA ) and a putative TonB‐dependent receptor ( sftP ). The SftP protein was localized in the outer membrane, and the arylsulfphotransferase was identified as an intracellular enzyme. Expression of sftR was repressed in the presence of inorganic sulphate, and the sftR gene was required for the expression of atsBC , atsRK and sftP–astA . An sftR mutant was unable to grow with aryl‐ or alkylsulphate esters in laboratory media and showed significantly reduced survival compared with the parent strain during incubation in Danish agricultural and grassland soils. This effect suggests that sulphate esters are an important sulphur source for microbes in aerobic soils and highlights the importance of the microbial population in the soil sulphur cycle.

Combined effect of the growth temperature and salinity of the medium on the accumulation of compatible solutes by Rhodothermus marinus and Rhodothermus obamensis - Zélia Silva; Nuno Borges; Lígia O. Martins; Robin Wait; Milton S. da Costa; H. Santos (Extremophiles, 1999)